Resultados de existência para as equações críticas de Klein-Gordon-Maxwell - Cunha, Patrícia Leal da (2011)
In this work we analyze the existence of radially symmetric solutions, positive solutions as well as the existence of ground state solutions for a class of Klein-Gordon-Maxwell equations when the nonlinearity exhibits critical behavior. For the positive and ground state solutions we prove existence results when a potential V is introduced. In order to obtain such results, we use variational methods